Peningkatan Minat Belajar Siswa dengan Model Pembelajaran Kooperatif Tipe TPS (Think, Pair and Share) Berbantuan Media Spin Neptune - Rama, Teodata; Anni Malihatul Hawa (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2026)
Interest in learning is a crucial element that influences students' success in the learning process at the elementary school level. However, initial research at Gedanganak 03 Public Elementary School indicates that the learning interest of second-grade students is still relatively low. The causes include the application of more conventional teaching methods, a lack of variety in learning models and media, as well as insufficient active student participation in the learning process. Therefore, innovative learning approaches are needed to create an interactive and enjoyable learning atmosphere. This study aims to measure the effectiveness of the cooperative learning model of Think, Pair, and Share (TPS) supported by Spin Neptune media on students' learning interest, as well as to identify the differences and improvements in students' learning interest before and after the implementation of this model. The study applies a quasi-experimental method with a pretest-posttest control group design. The population in this research includes all students of Gedanganak 03 Public Elementary School, while the sample consists of second-grade students from classes II A and II B. Data collection is conducted using a learning interest questionnaire, observations, interviews, and documentation. Data processing involves validity testing, reliability testing, normality testing, homogeneity testing, and hypothesis testing using the t-test. The research findings indicate a clear difference between the learning interest of students in the experimental class and the control class Keywords: Cooperative Learning Model, Think Pair Share (TPS), Spin Neptune Media, Learning Interest, Elementary School